The 21st-Century Humanitarian Crisis in the Perspective of al-Ghazali and Abbasid History: (Krisis Kemanusiaan Abad ke-21 dalam Perspektif al-Ghazali dan Sejarah Abbasiyah) - Azrian Isyfaul Fuadi; Iman Hidayatullah (Journal of Islamic Education and Intellectual Discourse (JIED), 2026)
This study discusses the humanitarian crisis of the 21st century by reviewing the historical experiences of the Abbasid Dynasty and the thoughts of Imam al-Ghazali. Globalisation, which has brought advances in science and technology while also giving rise to humanitarian problems such as social inequality, moral decadence, and spiritual disorientation, shows a pattern similar to the decline of Islamic civilisation during the Abbasid period. This study uses a qualitative approach with a literature review method. Data was collected from classical and contemporary literature, then analysed through content analysis and a historical-comparative approach. The results of the study show that the decline of the Abbasids was not only caused by external attacks, but also by internal crises in the form of weak morality, corruption, and a loss of spiritual orientation. Imam al-Ghazali's thoughts, particularly in Ihya 'Ulum al-Din, emphasise the importance of purifying the heart, strengthening morality, and integrating knowledge with faith and ethics as fundamental solutions to the humanitarian crisis. Thus, the historical lessons from the Abbasids and al-Ghazali's thoughts provide important reflections for modern global society to not only focus on material progress but also to build moral and spiritual foundations for the creation of a just and sustainable civilisation. Keywords: Humanitarian Crisis, Abbasid Dynasty, Imam al-Ghazali.